City of Big Shoulders : A History of Chicago - Spinney, Robert G. (Robert Guy) (Book collections on Project MUSE., 2020)
"This compact yet comprehensive account of Chicago's history links key events in the city's development, from its marshy origins in the 1600s to today's robust metropolis. Synthesizing a vast body of literature, Robert Spinney presents Chicago in terms of the people whose lives made the city-not only the tycoons and the politicians but also the hundreds of thousands of immigrants from all over the world who have kept the city working"--